ANALISIS KETAHANAN PANGAN RUMAH TANGGA TANI DI KABUPATEN MANOKWARI - JEFFRY E SIANIPAR; SLAMET HARTONO; RONAL TP HUTAPEA (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2012)
Increased production and income of farmers in the district of Manokwari will affect the purchasing power of farmers to food needs. Adequate food needs will have implications for the fulfillment of nutritional adequacy for farmers. Insufficient food needs can describe the level of food security at farm household. This study aims to determine and analyze the factors that influence the level of food security of farm households in the district of Manokwari.